Moral Aspects of Judaism, Christianity and Islam (Annual of the Faculty of Philosophy in Skopje, 2018)
In the modern society many factors influence the societal processes. There is nosocial sphere that can remain untouched by the changes that happen every single day. Besidesall the specifics of modern lifestyle, a particular one is the religion as one of the mostcomplex societal phenomena. The modern sociologists of religion share the opinion that inthe 21st century as well, in the era of globalization and internet-revolution, the religion isnot just losing its path, but is becoming even more established in the societal environment.In the context of religion, the emphasized moral aspects are very significant, especially thoseof the dominant monotheistic religions (Judaism, Christianity and Islam) as universal humanmoral values. By accepting these values, a person enriches himself.
Keywords: RELIGION; MORAL VALUES; JUDAISM; CHRISTIANITY; ISLAM